THE BASIS FOR DESIGN OF A DSP-BASED COINCIDENCE SPECTROMETER - PHAM , DINH KHANG; NGUYEN , XUAN HAI; NGUYEN, NHI DIEN; PHAM , NGOC TUAN; DANG , LANH; NGUYEN , DUC HOA; NGUYEN , AN SON (Nuclear Science and Technology, 2011)
Coincidence technique and the coincidence measurement systems have been developed and applied for over 40 years. Most of popular coincidence measurement systems were based on analog electronics techniques such as time to amplitude conversion (TAC) or logic selecting coincidence unit. The above-mentioned systems are relatively cumbersome and complicated to use. With the strong growth of digital electronics techniques and computational science, the coincidence measurement systems will be constructed simpler but more efficient with the sake of application. This article presents the design principle and signal processing of a simple two-channel coincidence system by a new technique called Digital Signal Processing (DSP) using Field Programmable Gate Arrays (FPGA) devices at Nuclear Research Institute (NRI), Dalat.